Clinical profile and outcome of children with haemophilia A: The Royal Hospital, Oman’s experience - AlRawahi Anood; AlGaithi Ibrahim; Al Riyami Fatma; Al Abri Maather; Al Shukaili Hajer; Al Rawahi Abdulhakim (The Journal of Haemophilia Practice)
Data on clinical characteristics and bleeding outcome of Omani children with haemophilia A (HA) is limited. This study aims to describe the clinical profile and outcome of Omani children with HA at the Royal Hospital from 2006 to 2019.